Physico-chemical composition and sensory quality of conilon coffee produced in Espírito Santo State and submitted to different processing forms Composição físico-química e qualidade sensorial de café conilon produzido no Estado do Espírito Santo e submetido a diferentes formas de processamento - Tarcísio Lima Filho (Semina: Ciências Agrárias, 2013)
Espirito Santo State is the largest producer of conilon coffee in Brazil. However, there is a lack of information about physico-chemical composition and sensory characteristics of this coffee submitted to different processing forms. Therefore, the objective of this work was to investigate physico-chemical and sensory characteristics of the Espirito Santo conilon coffee submitted to three forms of processing. The harvest was performed selecting only cherry grains, which were submitted to three forms of processing (dry process, semi dry process or wet process). Sensory analysis was performed by two professional classifiers. Analysis of moisture, pH and titratable acidity were determined in samples of raw and roasted coffee and aqueous extract were determined in samples of roasted coffee. The processing forms and types of grains did not differ in terms of pH and acidity. Natural and peeled coffee showed higher levels of aqueous extract. In sensory classification, all samples showed good overall evaluation. The use of raw material within the quality standards, grains of cherry type and the proper conduction of post-harvest stages allow the obtainment of a beverage with good sensory ratings and without changes in pH and acidity regardless the processing form used. Therefore, it is possible to obtain good quality beverages using dry processing, which is less expensive than the other types of coffee processing Apesar de o estado do Espírito Santo ser o maior produtor de café conilon brasileiro, pouco se sabe sobre a composição físico-química e características sensoriais desse café submetido a diferentes formas de processamento. Sendo assim, o objetivo deste trabalho foi realizar a caracterização físico-química e sensorial do café conilon capixaba submetido a três formas de processamento. A colheita foi realizada selecionando-se apenas grãos cereja, que foram submetidos a três formas de processamento (via seca, via úmida sem fermentação ou via úmida com fermentação). A análise sensorial foi realizada por dois julgadores classificadores profissionais. Em amostras de café cru e torrado foram realizadas análises físico-químicas de umidade, pH e acidez titulável total e o extrato aquoso foi determinado apenas para amostras de café torrado. As formas de processamento e tipos de grãos apresentaram médias de pH e acidez estatisticamente iguais. Os cafés natural e descascado apresentaram maiores teores de extrato aquoso. Na classificação sensorial, todas as amostras apresentaram boa nota global. A utilização de matéria-prima dentro dos padrões de qualidade, o processamento de apenas grãos cereja e a realização adequada das etapas pós-colheita possibilitam a obtenção de uma bebida com boa classificação sensorial e sem alterações de pH e acidez, independentemente da forma de processamento utilizada. É possível obter bebidas dentro dos padrões de qualidade utilizando o processamento via seca, processamento menos custoso que os demais.